2020
DOI: 10.1186/s13041-020-00694-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and methylation status of selected retrotransposition competent L1 loci in amyotrophic lateral sclerosis

Abstract: Long interspersed element-1 (LINE-1/L1) is the only autonomous transposable element in the human genome that currently mobilises in both germline and somatic tissues. Recent studies have identified correlations between altered retrotransposon expression and the fatal neurodegenerative disease amyotrophic lateral sclerosis (ALS) in a subset of patients. The risk of an individual developing ALS is dependent on an interaction of genetic variants and subsequent modifiers during life. These modifiers could include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Our group has described the extra burden of L1 activity as associated with PD [12]. We have also described the increased expression of TE elements in different diseases [13][14][15]. These data indicate that TEs have an important impact on the inheritance or progression of diseases.…”
Section: Introductionmentioning
confidence: 80%
“…Our group has described the extra burden of L1 activity as associated with PD [12]. We have also described the increased expression of TE elements in different diseases [13][14][15]. These data indicate that TEs have an important impact on the inheritance or progression of diseases.…”
Section: Introductionmentioning
confidence: 80%
“…In this cohort 70 of these L1s were detected as polymorphic; 40 of which were intact (see Additional file 4 : Table S4 for coordinates and insertion allele frequencies of each L1). Three of the polymorphic L1s identified in our analysis had been genotyped for their presence/absence using PCR amplification in our previous study [ 25 ]. The intact L1s had lower insertion allele frequencies (IAF) compared to the non-intact loci, for example non-intact L1s had a significantly higher proportion of L1s with an IAF > 0.75 compare to intact loci (50% vs 22.5%, p = 0.03) (Additional file 6 : Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…This could be related to regulation of L1s by CpG methylation, for example a recent study showed that this L1 located on chr22 is hypomethylated in the liver compared to the heart and hippocampus [ 38 ]. Our previous work analysing the methylation status of 6 highly active RC-L1s in the motor cortex identified a reduction in the DNA methylation over these elements in ALS brains compared to controls [ 25 ]. Five of these elements located in the reference genome were also analysed as part of this study quantifying their expression levels and found that four of these L1s were expressed, however they were not part of the group of L1s responsible for the majority of the expression observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, TE subfamilies are species specific, but they rely on the same molecular mechanisms for their control and propagation [ 132 ], notably epigenetic mechanisms, including CpG DNA methylation. Indeed, genomes evolved defenses against their detrimental potential, and TE are generally silenced by DNA methylation and heterochromatin marks such as H3K9me3, acting as major barrier against their activation [ 133 , 134 , 135 , 136 ]. Thanks to the efforts of recent studies, TDP-43 has recently been shown to play a role in regulating them at several levels.…”
Section: Tdp-43 Role In Chromatin Remodeling and Transcriptionmentioning
confidence: 99%